CASE-CONTROL RETROSPECTIVE STUDY ON CARDIOVASCULAR DISEASE RISK AND QUALITY OF LIFE AMONG MALAY ADULTS - ERL, MO MIN; ALI, ASMA'; RAHIM, ARNIE A.; AMAN, ANAM; HARITH, SAKINAH; MOHD YUSOF, HAYATI (Malaysian Applied Biology, 2019)
In recent years, cardiovascular disease (CVD) has become the top cause of mortality, morbidity, and hospitalization in Malaysia. This study aimed to identify the most significant CVD risk factor and protective factor among Malay adults in Kuala Terengganu, as well as to compare the quality of life between case and control groups. A case-control study via self-administered questionnaire was carried out among 130 respondents aged 23 to 56 years in Universiti Malaysia Terengganu (UMT) and Nursing College Kuala Terengganu to compare past exposure (retrospective) between case and control groups to CVD risk. In the present study, 68 of them were in a case group with high blood cholesterol (total cholesterol [TC] > 5.18 mmol/L), while the other 62 were in a control group with the normal range of blood cholesterol (total cholesterol [TC] < 5.18 mmol/L). Purposive sampling was first applied to select the respondents in Kuala Terengganu. Then, consecutive sampling and quota sampling were performed in the study locations to recruit respondents, considering the type of respondents (case or control group) as a factor. The data were analysed using Independent-Samples t-test, Mann-Whitney U test, Chi-Square test and odds ratio (OR). The findings show no significant differences (p > 0.05) between the two groups in terms of CVD risk factors. However, by comparing the food frequency consumption scores, their fish consumption levels were found to be significantly different (p = 0.010). The control group had higher consumption (with a score of 60.8) compared to the case group (with a score of 50.8). Overweight or obesity was the only significant risk factor (OR: 2.13, 95% confidence interval [CI]: 1.06 to 4.29), while the only significant protective factor was the absence of any chronic diseases (OR: 0.00, 95% CI: 0.00 to 0.03), which were found to be associated with CVD, such as hypertension, diabetes mellitus and stroke. Furthermore, the quality of life of the control group was higher than that of the case group, but this difference was not significant (p > 0.05). Overweight or obesity is a major risk factor of CVD, while the absence of any chronic diseases is a major protector factor.